Human-environment interaction in the hinterland of Ephesos – As deduced from an in-depth study of Lake Belevi, west Anatolia. (15th September 2020) - Stock, Friederike; Laermanns, Hannes; Pint, Anna; Knipping, Maria; Wulf, Sabine; Hassl, Andreas R.; Heiss, Andreas G.; Ladstätter, Sabine; Opitz, Stephan; Schwaiger, Helmut; Brückner, Helmut
Abstract: Lacustrine sediments are important archives for high resolution palaeoenvironmental reconstructions of the Holocene. Despite the density of ancient cities and settlements along the western coast of Turkey, the archives from coastal lakes in this area have until now not been recognized to their fullest potential and are, therefore, only poorly studied. The exceptional geo-bio-archive of Lake Belevi is located close to the ancient city of Ephesos in western Turkey. Two sediment cores have been analysed using geochemical, sedimentological, microfaunal, palynological, and archaeoparasitological methods. The in-depth study of these Holocene deposits is supported by a robust age-depth model that used 33 radiocarbon dates and tephrochronology. The results reveal the existence of a freshwater lake in the Early Holocene which turned brackish when the rising sea level connected it with the sea. The delta evolution of the Küçük Menderes led to the re-establishment of a freshwater lake. The natural vegetation was represented by open oak woodlands. There are hints for first agricultural activities in the environs of Belevi as early as 8000 cal yr BP. Intensive cultivation of Olea is proven since 3000 cal yr BP. Starting during the 3rd millennium BP, the human impact with enhanced deforestation activities and correlative high sedimentation rates is attested for sites such as Belevi (Ephesos), Elaia (Pergamon) and Miletos. For the first time, tephra from the eruption of Minoan Santorini has been identified in the environs of Ephesos. This ash covered the vegetation by a thick layer, wherefore low-growing plants were strongly affected. The comparison between the results from the quasi natural area of Lake Belevi and the area around the city of Ephesos gives insights into the development and use of the landscapes, the environmental changes as well as the duration and intensity of the human impact. Highlights: Multi-proxy analysis of two drill cores in Lake Belevi close to ancient Ephesos. Palynological record of the last 8500 years for Lake Belevi, Western Turkey. Human impact from 3rd millennium BP on. Detection of the Minoan Ash of the Santorini eruption (3560 ± 15 cal yr BP).